2003
DOI: 10.1002/pd.628
|View full text |Cite
|
Sign up to set email alerts
|

Absence of fetal nasal bone and aneuploidies at first‐trimester nuchal translucency screening in unselected pregnancies

Abstract: The absence of NB at 11 to 14 weeks is more frequent in fetuses with trisomy 21 and other aneuploidies than in normal karyotype fetuses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
1
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(63 citation statements)
references
References 17 publications
3
57
1
2
Order By: Relevance
“…During statistical analysis, a comparison of the results with the risk cut-off level of 1:250 for standard screening was performed and revealed DR and FPR of 87% and 4.3%, respectively, and of 90% and 2.5%, respectively with additional NB evaluation [10]. Zoppi et al, investigated NT and NB in 5532 fetuses [1], and found absent NB in 70%, 80% and 66% of the fetuses with Down's, Edwards and Turner's syndromes, respectively, as well as 0.2% of fetuses with normal karyotype [1]. According to Otano et al [11], agenesis of the nasal bone is diagnosed in 60% of T21 and 0.6% of healthy fetuses, what is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During statistical analysis, a comparison of the results with the risk cut-off level of 1:250 for standard screening was performed and revealed DR and FPR of 87% and 4.3%, respectively, and of 90% and 2.5%, respectively with additional NB evaluation [10]. Zoppi et al, investigated NT and NB in 5532 fetuses [1], and found absent NB in 70%, 80% and 66% of the fetuses with Down's, Edwards and Turner's syndromes, respectively, as well as 0.2% of fetuses with normal karyotype [1]. According to Otano et al [11], agenesis of the nasal bone is diagnosed in 60% of T21 and 0.6% of healthy fetuses, what is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Trisomy 21 (Down syndrome) is one of the most common chromosomal defects diagnosed prenatally [1]. Phenotypic characteristics of this disease were described by John Langdon Down in 1866 [2], and are currently used as markers in prenatal ultrasound [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence/hypoplasia of the nasal bone, which can be determined in the first 1 and second 2 trimesters of pregnancy and would seem to be a strong marker of trisomy 21, has been the subject of lively debate in this and other journals 3 .…”
mentioning
confidence: 99%
“…Detection of the presence or absence of a nasal bone has been found to be of value in the assessment of aneuploidy in the first trimester of pregnancy (risk assessment for trisomy 21). [16][17][18][19][20] Cicero et al 20 reported that the nasal bone was absent in 113 (0.6%) of the 20,165 chromosomally or phenotypically normal fetuses and in 87 (62.1%) of the 140 fetuses with trisomy 21. 3D sonography allows a midsagittal section of the fetal face to be obtained by utilizing the three orthogonal planes, and avoids the pitfall of obtaining a parasagittal view, which could lead to false-negative results.…”
Section: Facial Abnormalitiesmentioning
confidence: 99%